Information technologies for the study of lexical and grammatical norms in the course “Ukrainian language for professional purposes” - L. Radomska; M. Moshnoriz (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки)
The article analyzes the current aspects of studying lexical and grammatical norms in the classes of the course “Ukrainian language for professional purposes” using information technologies. The authors consider the issue of developing and improving lexical and grammatical competence of higher education students as a requirement and basis for the culture of oral speech of a specialist. The purpose of the article is to analyze theoretical and methodological ways of studying lexical and grammatical norms using information technologies in the classes of the course “Ukrainian language for professional purposes”, as well as to study the problem of improving linguistic and communicative competence in higher education students in the context of the educational needs of the modern generation of “zoomers” in Ukraine, which, in addition to the global challenges associated with the COVID-19 pandemic, is forcibly exposed to the influence of social and demographic changes associated with the Russian-Ukrainian war.